2021
DOI: 10.1371/journal.pone.0248679
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health technologies supporting colonoscopy preparation: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background Mobile health (mHealth) technologies are innovative solutions for delivering instructions to patients preparing for colonoscopy. Objective To systematically review the literature evaluating the effectiveness of mHealth technologies supporting colonoscopy preparation on patient and clinical outcomes. Methods MEDLINE, EMBASE, CINAHL and CENTRAL were searched for randomized controlled trials (RCTs) that evaluated the effectiveness of mHealth technologies for colonoscopy preparation on patient and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Consistent with improved rates of adequate bowel preparation, supplemental education also improved bowel quality scores ( Fig 6 ). This is in line with a recent meta-analysis [ 56 ] that found that mobile health technology is associated with better bowel preparation quality scores. This is also in line with a meta-analysis published in 2021 [ 40 ], which showed that reinforced education increases colonoscopy BBPS scores and decreases OBPQS scores.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with improved rates of adequate bowel preparation, supplemental education also improved bowel quality scores ( Fig 6 ). This is in line with a recent meta-analysis [ 56 ] that found that mobile health technology is associated with better bowel preparation quality scores. This is also in line with a meta-analysis published in 2021 [ 40 ], which showed that reinforced education increases colonoscopy BBPS scores and decreases OBPQS scores.…”
Section: Discussionsupporting
confidence: 91%
“…Our meta-analysis showed that supplementary education had no statistically significant difference in reducing the nonattendance rate of outpatient colonoscopy (9.5% vs 11.5%, RR:0.82, 95% CI: 0.72 to 0.94, I 2 = 38%, p = 0.10). A recently published meta-analysis also shows that mobile health technology cannot reduce the no-show rate of colonoscopy [ 56 ]. It is worth noting that there was no obvious heterogeneity (I 2 = 38%, p = 0.09) in the research.…”
Section: Discussionmentioning
confidence: 99%
“…Screening organizers may also consider applying modern technology such as a smartphone app or telemedicine at many steps of FIT screening, such as consultation about eligibility for CRC screening, notification of FIT results, scheduling colonoscopy, pathology result notification, and advising about the timing of surveillance colonoscopy, to facilitate CRC screening during the COVID pandemic ( Azulay et al, 2019 ; El Bizri et al, 2021 ). In fact, telehealth technology has been boosted and widely adopted in the past year owing to the COVID-19 pandemic, and many healthcare systems have observed a tremendously increased number of telemedicine visits ( McCall, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During clinical colonoscopy for children, the examination is often performed under general anesthesia, considering the acceptance degree, physical dosage, and tolerance of children. Intestinal examination preparation should be arranged according to child's age, physical condition, clinical symptoms, digestive status, and examination willingness [ 6 ]. At present, there are many preparation programs, among which physiological saline enema, oral magnesium sulfate, or mannitol are important drugs for adults to clean the intestine before examination.…”
Section: Introductionmentioning
confidence: 99%